Antibiotics : not your cold fix - Ravindaran, Clara (2019)
This report presents ‘ Not Your Cold Fix’ , Singapore’s pioneering campaign addressing patients’ expectations for antibiotics for Upper Respiratory Tract Infections (URTIs) among parents of children aged between 0 to 12 years old. The campaign ultimately aims to decrease expectations in parents for antibiotics in treating their child’s cold - that are motivated by a perceived sense of urgency, lack of awareness of the ineffectiveness of using antibiotics for the cold, low self-efficacy in managing cold symptoms and low risk perception of treating colds with antibiotics. Strategies such as making specific information accessible through familiar platforms, engaging parents through their children, and empowering parents to feel more in control of their child’s illness were employed to achieve the campaign objectives. Framed by the Theory of Planned Behaviour (TPB), through improving knowledge levels of parents about the inefficacy of antibiotics for colds and also improving social norms of not asking for antibiotics, the campaign aims to improve the appropriate behaviour among parents to ask for advice instead of antibiotics for their child’s URTI.